PENGARUH KUALITAS PELAYANAN, FASILITAS DAN HARGA TERHADAP KEPUASAN PASIEN PRAKTEK BIDAN MEGAWATI - Sebastian, David; Tin Agustina Karnawati; Moh. Bukhori (Faculty of Economics and Business, Universitas Warmadewa, 2024)
The number of independent midwifery practices has been steadily increasing each year, particularly in the area of North Tambun sub-district, necessitating the need for competitiveness to compete with other independent midwifery practices. This research aims to determine the influence of Service Quality, Facilities, and Price on Patient Satisfaction in North Tambun sub-district. The respondents of this study were 100 outpatient patients at Bidan Megawati Debataraja's clinic. The research utilized the accidental sampling method, employing a Google Form questionnaire through a quantitative analysis approach processed using SPSS 25. The statistical data analysis used Classic Assumption Test, Determinant Test, Multiple Linear Regression Analysis, and Hypothesis Test. The results of the study indicate that there is a positive and significant partial influence of service quality on patient satisfaction. However, there is no significant positive partial influence of facilities on patient satisfaction. Additionally, there is a positive and significant partial influence of price on patient satisfaction. Simultaneously, there is a positive and significant influence of service quality, facilities, and price on patient satisfaction.